The Degree of Agreement between Manual and Digital Histological Evaluation of Immunohistochemical Expression of Estrogen and Progesterone Receptors in Breast Carcinoma - Hameda Abd-Al Mahdi Ghazi Ghazi (Journal of Global Pharma Technology, 2017)
Background Malignant neoplasm involving the breast is by far one of the most frequent cancers that affect mankind. Globally, it is estimated that breast cancer accounts for about 25% of all cancers affecting women. Carcinoma of the breast is heterogeneous; however, they all share the common origin from the terminal duct lobular unit. They are generally classified into ducal and lobular. The three gold standard immunohistochemical makers, nowadays, are progesterone and estrogen receptors (PR and ER) and her2neu. Other markers like p53 and bcle2 expression are also important. The study of PR and ER receptors permits the decision of adding and adjunct mode of treatment, hormonal treatment. Aim of the study the objective of this study was to assess automated digital study of immunohistochemical markers as a substitute for the original manual method. Materials and methods: The present study included 35paraffin embedded, formalin fixed histological blocks of breast carcinoma. The duration of the study extended from January 2017 to June 2017 and was conducted in the teaching laboratories of College of Medicine, Al-Qadissiyah Univerist, Al-Diwaniayah province, Iraq. The paraffin blocks were retrieved from the teaching laboratories of Al-Diwaniyah teaching hospital, Al-Diwaniayah province, Iraq. Results: Following conversion into positive and negative cases, matching was assessed using kappa agreement statistic and the results were as following: number of positive ER cases were 14 and 16 according to manual and digital scoring, respectively; whereas the number of positive PR cases were 15 and 17 according to manual and digital scoring, respectively, as shown in table 3 and 4. The degree of agreement between manual and digital scoring was 0.87, considered good, in both ER and PR expression status. Conclusion Digital scoring appears to be faster than and as accurate as manual scoring; however it needs to be correlated with clinical prognosis of breast carcinoma.